Optimizacija postopka izračunavanja kovinskega vložka z uporabo računalniškega programskega paketa CHARGE-PRO - Koroušić, Blaženko (Materiali in tehnologije, 2001)
The advantages of using thedatabank system with the CHARGE-PRO software program to calculate the number of charge-mix operations in the steelshop in the production of different types of steel grades, especially for high-alloyedsteels, are described. The potential applications for the CHARGE-PRO routines in a program for handling complex charge-mix calculations is ectremely diverse. In recent years it has become obvious that many programs(especially for frame computers) would benefit from the ability to make charge calculations. The CHARGE-PRO software was developed for small and medium foundaries and steelworks and is based on improved linear programming routines and enhanced by a set of practical interface routines to allow their easy use in practise.
Keywords: proizvodnja jekla; kovinski vložek; linearno programiranje